The influence of pH on dissolved organic matter fluorescence in inland waters. Issue 13 (17th March 2022) - Groeneveld, M.; Catalán, N.; Einarsdottir, K.; Bravo, A. G.; Kothawala, D. N.
Abstract : Fluorescence is an easily available analytical technique used to assess the optical characteristics of dissolved organic matter (DOM). Abstract : Fluorescence is an easily available analytical technique used to assess the optical characteristics of dissolved organic matter (DOM). Despite widespread use, there has been some confusion about how robust fluorescence spectroscopy is to differences in solution pH. Here we assess fluorescence characteristics of three natural water samples and one commercially available standard (Nordic Reservoir) by modifying the pH across a range from 3.5 to 9.0 at 0.5 pH increments. We used two statistical approaches to assess if fluorescence intensity shifted significantly across this pH range. We identified that humic-like and protein-like fluorescence was largely stable within the pH range of 5.5 to 7.5, which represents 80% of Swedish lakes and streams. Likewise, we found that the three commonly used fluorescence indices were robust across the full pH range tested with the exception of the humification index, which had a narrower range of stability. The commerical humic substance sample was highly unstable with changes to pH in the regions of protein-like fluorescence being particularly sensitive. One of our conclusions is that differences in fluorescence intensity in the pH range of 5.5 to 7.5, typical for most inland waters, are generally minor. We recommend adjusting the pH when samples fall outside this region and to be especially careful in interpreting results from commercial humic substances.